The use of Slovak Simmental breed in suckler beef system - Vavrišínová, Klára; Hozáková, Katarína; Juhás, Peter; Janíček, Martin; Margetín, Milan; Obtulovič, Peter (Animal welfare, Ethology and Housing Systems (AWETH), 2020)
The aim of this study was to monitor productive characteristics of Slovak Simmental breed and crossbreeds of different proportion (>50% of Slovak Simmental breed) in the system of suckling beef in Slovakia. Study evaluated a total of 932 animals for growth parameters and 75 animals for carcass characteristics. Analysing of calving ease showed 4.95% proportion of calving with assistance (calving ease score 2 from 4 point scale). These were found in calving of one gender – heifers. All other recorded calving was without need of assistance. Analysis of variance confirmed highly significant influence of the sire on calving difficulty (P
Keywords: calving season; carcass class; growth parameters; Slovak Simmental breed; suckling beef